Development of a MATLAB GUI for Sizing and Techno-Economic Analysis of Grid-Connected Photovoltaic Systems at Taman Universiti, Parit Raja, Batu Pahat. - Rusli, Nur Shafiqah; Mohamad Nor, Ahmad Fateh (Evolution in Electrical and Electronic Engineering, 2025)
This project presents the development and implementation of a MATLAB-based Graphical User Interface (GUI) tool to facilitate the sizing of grid-connected photovoltaic (GCPV) systems for single-story houses in Taman Universiti, Parit Raja. The GUI simplifies the potentially complex process of PV system sizing through the combination of energy, budget, architectural, and regulatory constraints into a single interactive tool. The GUI features 5 tabs that guide users through module selection, system design, and techno-economic analysis based on Net Energy Metering (NEM 3.0). The tool serves as a convenient solution for homeowners and non-technical people to maximise the GCPV investments. The REC Alpha Pure-R Series (430W) was the most suitable PV module for this location, considering factors such as cable efficiency, mismatch factor, degradation factor, average temperature factor, and peak sun hours. Similarly, the inverter selected for this system is the Huawei SUN2000-2KTL-M0 (3000W), as it matches the required inverter power of 2324.32W and provides a sufficient safety margin. The system is designed with 2 strings, each comprising 3 PV modules, connected to two separate maximum power point trackers (MPPTs), labelled as MPPT A and MPPT B.